Coastal-marine environments of Parque Nacional Corcovado, Puntarenas, Costa Rica - Cortés, Jorge (1996)
Parque Nacional Corcovado is famous for its terrestrial ecosystems but also has important but unappreciated coastal- marine environments. These environments, which have not been studied, include sandy beaches, rocky out-crops, soft and hard bottoms and coral reefs. We describe three intertidal rocky sites. list the coral species, and describe several coral communities from Corcovado. Species composition and distribution on the intertidal zone are similar to other areas on the Pacific coast of Costa Rica. Eleven species of scleractinian corals were found in the Park, a richness equivalent to other reefs in the country. The most important species were Pocillopora damicornis, Pocillopora elegans and Porites lobata. Pocillopora reefs were found in Corcovado, the y are common in other parts of the eastern Pacific but rare in Costa Rica. The Park is an important refuge for species of commercial value that have been depleted from most of the coast. This National Park, together with most of the other protected areas in the country. e.g. Isla del Caño. Santa Rosa and Manuel Antonio, have become the sole reservoirs and sources of larvae, juveniles and adults of many species for adjacent areas